Sural and medial plantar nerve conduction study in the diagnosis of subclinical diabetic neuropathy - Mahmoud M Hasan; Abd E Shokry; Sara K Mohamad; Ali F El (Wolters Kluwer Medknow Publications, 2021)
Background and Aim Diabetic peripheral neuropathy is one of the most challenging complications of diabetes mellitus. A large number of patients have subclinical neuropathy at the time of detection of diabetes. Proper detection of subclinical diabetic neuropathy is important to prevent more complications. When the symptoms start, there are not many effective therapeutic treatments. Nerve conduction studies (NCS) are known to be sensitive, reliable, noninvasive, and easy to perform to study diabetic neuropathy. Study of the medial plantar and sural nerves can test the most distal parts of the nerves and can be considered an alternative method for the diagnosis of polyneuropathy in the early stages. The aim of this work is to study the utility of both medial plantar and sural nerve conduction in the early diagnosis of diabetic polyneuropathy. Patients and methods Twenty diabetic asymptomatic patients and 20 healthy volunteers of both sexes were included. Their ages ranged between 26 and 44 years and 24 and 46 years, respectively. NCS of the medial plantar and sural nerves for all the patients and control groups is performed using the antidromic method of stimulation for sural nerve and orthodromic stimulation for the medial plantar nerve. Results There were significant changes in the sensory study of both medial plantar and sural nerves of neurologically asymptomatic diabetic patients compared with the control. Conclusion NCS of both medial plantar and sural nerves aids in the detection of subclinical diabetic polyneuropathy.